2010
DOI: 10.1007/s11205-010-9607-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Changes in Living Conditions on Well-Being: A Prospective Top–Down Bottom–Up Model

Abstract: Well-being, Life-satisfaction, Housing satisfaction, Moving, Prospective study, Adaptation theory,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
44
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 49 publications
10
44
1
2
Order By: Relevance
“…Over time, however, the novelty will wear off and subjective well-being will return to its previous levels. The hedonic treadmill theory does not predict adaptation in housing satisfaction judgements as these should not be influenced by positive/negative affect (Nakazato et al 2011).…”
Section: The Dynamic Aspect Of the Relationshipmentioning
confidence: 92%
See 3 more Smart Citations
“…Over time, however, the novelty will wear off and subjective well-being will return to its previous levels. The hedonic treadmill theory does not predict adaptation in housing satisfaction judgements as these should not be influenced by positive/negative affect (Nakazato et al 2011).…”
Section: The Dynamic Aspect Of the Relationshipmentioning
confidence: 92%
“…Using Australian Panel Data, Frijters et al (2011) found a positive effect of moving house (for all reasons) on life satisfaction but this effect lasted for 6 months only. Nakazato et al (2011) examined the effect of moving for housing related reasons on the life satisfaction and housing satisfaction of 3658 participants in the German Socio-Economic Panel. In this scenario, moving house led to an increase in housing satisfaction but this was only partially sustained over the 5 years post-move.…”
Section: The Dynamic Aspect Of the Relationshipmentioning
confidence: 99%
See 2 more Smart Citations
“…Wilson and Gilbert (2003) (Wirtz et al 2003), hemodialysis (Riis et al 2005), colostomy (Smith et al 2006), income (Kahneman et al 2006), gambles (Kermer et al 2006), experiencing relationship breakups (Eastwick et al 2008), unemployment (Dolan and Powdthavee 2011), and housing (Nakazato et al 2011).…”
Section: Introductionmentioning
confidence: 99%